2019
DOI: 10.18186/thermal.623211
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Generation Rate in a Microscale Thin Film

Abstract: This paper presents a new formulation of the rate of entropy generation in thin films whose thickness is of the order of the mean-free-path or less. In this relation, an expression for the gradient of the equivalent equilibrium temperature is proposed that is a function of the gradient of the phonon intensity at any point inside the thin film. It is shown that the proposed expression reduces to the familiar gradient of the thermodynamic temperature in the diffusive limit. Furthermore, the new formulation is us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The literature review shows that the entropy generation in laminar mixed convection in cavities is a subject that remains to be explored. Different studies were studied and reported in the literature [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The literature review shows that the entropy generation in laminar mixed convection in cavities is a subject that remains to be explored. Different studies were studied and reported in the literature [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The same formulation has been used for entropy generation analysis of laminar and turbulent flows in ducts subjected to a constant temperature, heat flux, and heat exchangers [21][22][23][24]. More rigorous work has been carried out by Chamka for various flow and geometrical conditions [25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%